The Economic Impact of Environmentally Sustainable Transport in Germany - Burkhard Schade; Werner Rothengatter (European Journal of Transport and Infrastructure Research, 2004)
The economic assessment of the Environmentally Sustainable Transportation (EST) scenarios developed throughout this paper are part of Phase 3 of the overall project, which is on social and economic assessment and on devising packages of instruments that - if implemented - would result in attaining EST.